(untitled) (CR. Conservación y Restauración, 2025)
Within the problem of illicit trafficking of cultural heritage, the main protagonists are the communities that hold cultural property and those who steal it. However, collectors are also key players in the operation of this trade. In this article, responsibility in collecting refers to considering the social damage that the absence of cultural heritage causes in the communities where it is stolen, as well as the crime for the illegality of its trade, stipulated in the Ley Federal de Monumentos y Zonas Arqueológicos, Artísticos e Históricos. Private collecting preserves part of Mexico’s cultural –material– heritage and at the same time encourages its theft due to the demand for antique objects in the art market. Therefore, reflecting on the motivations of collectors and practicing collecting with an ethic of responsible acquisition is crucial to combat the illicit trafficking of cultural property.